The âexpert patientâ approach for non-communicable disease management in low and middle income settings: When the reality confronts the rhetoric - Yue Xiao (KeAi Communications Co., Ltd., 2015)
This paper seeks to explore the relevance between the Western âexpert patientâ rhetoric and the reality of non-communicable diseases (NCDs) control and management in low and middle income settings from the health sociological perspective. It firstly sets up a conceptual framework of the âexpert patientâ or the patient self-management approach, showing the rhetoric of the initiative in the developed countries. Then by examining the situation of NCDs control and management in low income settings, the paper tries to evaluate the possibilities of implementing the âexpert patientâ approach in these countries. Kober and Van Damme's study on the relevance of the âexpert patientâ for an HIV/AIDS program in low income settings is critically studied to show the relevance of the developed countries' rhetoric of the âexpert patientâ approach for the reality of developing countries. In addition, the MoPoTsyo diabetes peer educator program is analyzed to show the challenges faced by the low income countries in implementing patient self-management programs. Finally, applications of the expert patient approach in China are discussed as well, to remind us of the possible difficulties in introducing it into rural settings. Keywords: Non-communicable disease, Expert patient, Control, Management